Highly water-absorbent resin and method for producing same

By using water-soluble vinyl unsaturated monomers and crosslinking polymers that partially neutralize acid groups in superabsorbent resins, and adding calcium detoxifiers and surface crosslinking agents in the production process, the problem of difficulty in reducing residual monomer concentrations at the same time in the prior art, inhibiting bacterial growth and removing foul odors is solved, and efficient water retention and pressure absorption performance are achieved.

JP2025511595AActive Publication Date: 2025-04-16LG CHEM LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024556531
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-12-21
Filing Date
2023-12-22
Publication Date
2025-04-16
Estimated Expiration
2043-12-22

AI Technical Summary

Technical Problem

When used in sanitary products, it is difficult to achieve the effect of reducing residual monomer concentration, inhibiting antibacterial growth and removing odor while maintaining good water retention and pressure absorption performance.

Method used

A crosslinked polymer containing water-soluble vinyl unsaturated monomer and partially neutralized acidic groups is adopted, and calcium detoxifier is added during the production process, and the surface is further crosslinked by the surface crosslinking agent, controlling the excess heat starting dose to reduce the residual monomer concentration while maintaining good physical properties.

Benefits of technology

The application of superabsorbent resin in sanitary products is achieved, reducing the concentration of residual monomers, significantly improving the antibacterial growth inhibition and deodorization effect, while maintaining water and pressure absorption performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025511595000001_ABST
    Figure 2025511595000001_ABST
Patent Text Reader

Abstract

The present invention provides a superabsorbent resin having excellent water retention and pressurized water absorption capabilities due to a reduction in residual monomers in the superabsorbent resin, while exhibiting improved bacterial growth inhibition and deodorizing properties, and also exhibiting excellent color characteristics due to suppressed discoloration, and a method for producing the same.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0183171 dated December 23, 2022 and Korean Patent Application No. 10-2023-0188595 dated December 21, 2023, and all contents disclosed in the documents of said Korean patent applications are incorporated herein by reference.

[0002] The present invention relates to a superabsorbent resin that exhibits excellent water retention and pressurized water absorption capabilities due to a reduction in residual monomers in the superabsorbent resin, while exhibiting improved bacterial growth inhibition properties and deodorizing properties, and also exhibits excellent color characteristics due to suppression of discoloration, and a method for producing the same. [Background technology]

[0003] Super absorbent polymer (SAP) is a synthetic polymeric substance that has the ability to absorb 500 to 1,000 times its own weight in water, and each developer has given it a different name, such as SAM (Super Absorbency Material) or AGM (Absorbent Gel Material). Such super absorbent polymers first came into practical use as sanitary products, and are now widely used in a wide range of applications, from sanitary products such as baby diapers to soil rehydration agents for gardening, water-stopping materials for civil engineering and construction, seedling sheets, freshness-preserving agents in the food distribution industry, materials for packs, and electrical insulation.

[0004] In particular, superabsorbent polymers are most widely used in sanitary products or disposable absorbent products such as baby diapers and adult diapers. In particular, when applied to adult diapers, secondary odors caused by bacterial growth cause a problem of great discomfort to consumers. In order to solve such problems, attempts have been made to introduce various bacterial growth inhibitors, deodorizing or antibacterial functional components into superabsorbent polymers.

[0005] However, when introducing antibacterial agents that inhibit bacterial growth into a superabsorbent polymer, it has not been so easy to select and introduce an antibacterial component that exhibits excellent bacterial growth inhibition and deodorizing properties, is harmless to the human body, is economical, and does not deteriorate the basic physical properties of the superabsorbent polymer.

[0006] For example, attempts have been made to introduce antibacterial components containing antibacterial metal ions such as silver, copper, and zinc, such as copper oxide, into superabsorbent polymers. Such antibacterial metal ion-containing components can destroy the cell walls of microorganisms such as bacteria, and kill bacteria having enzymes that can induce odors in the superabsorbent polymer, thereby imparting deodorizing properties to the superabsorbent polymer. However, the metal ion-containing components are classified as biocide substances that can kill even microorganisms that are beneficial to the human body. As a result, when the superabsorbent polymer is applied to sanitary products such as diapers for children or adults, the introduction of the metal ion-containing antibacterial components is avoided to the greatest extent possible.

[0007] In the past, when introducing antibacterial agents that inhibit bacterial growth into superabsorbent resins, the antibacterial agents were mainly blended in small amounts into the superabsorbent resins. However, when using such blending methods, it was difficult to maintain the bacterial growth inhibition properties uniformly over time. Moreover, such blending methods had the disadvantages of causing non-uniform application and detachment of the antibacterial agent components during the process of mixing the superabsorbent resin and the antibacterial agent, and of needing to install new equipment for the blending.

[0008] Meanwhile, for superabsorbent polymers to be used as sanitary materials, the residual monomer (RM) concentration must be low. If the RM is high, the superabsorbent polymer cannot fully demonstrate its water-absorbing properties, such as its water-retaining capacity and pressurized water-absorbing capacity. In order to reduce the RM concentration, it is basic to use acrylic acid, which has a low dimer concentration, as the main raw material, and methods such as increasing the amount of thermal initiator added or adding additional additives that can reduce the RM concentration are used. However, in this case, there are problems such as deterioration of other physical properties of the superabsorbent polymer and a complicated process of adding the additional additives. In particular, when the amount of thermal initiator added is increased, there is a problem that the manufactured superabsorbent polymer turns yellow.

[0009] In addition, a chelating agent is used during the manufacture of a superabsorbent resin as a method for suppressing the growth of ammonia-generating bacteria and improving the deodorizing performance of the superabsorbent resin. However, when a chelating agent is used, there is a problem that the content of residual monomers in the superabsorbent resin produced is relatively increased compared to when a chelating agent is not used.

[0010] As a result, there is a continuing demand for the development of technologies related to superabsorbent polymers that can reduce the residual monomer content in the superabsorbent polymers and thereby exhibit excellent bacterial growth inhibition and deodorizing properties without compromising basic physical properties and water absorption performance. Summary of the Invention [Problem to be solved by the invention]

[0011] Therefore, the present invention provides a superabsorbent resin that exhibits excellent water retention and pressurized water absorption capabilities by reducing residual monomers in the superabsorbent resin, while exhibiting improved bacterial growth inhibition and deodorizing properties, and that exhibits excellent color characteristics by suppressing discoloration, and a method for producing the same.

[0012] The present invention also provides an article, specifically a sanitary product, which contains the superabsorbent polymer and thus exhibits excellent water retention and pressurized water absorption capabilities while also exhibiting improved bacterial growth inhibition and deodorizing properties. [Means for solving the problem]

[0013] In order to solve the above problems, the present invention provides a base resin powder comprising a first crosslinked polymer of a water-soluble ethylenically unsaturated monomer having at least a partially neutralized acidic group, and a chelating agent; and a surface crosslinked layer formed on the base resin powder and including a second crosslinked polymer obtained by additionally crosslinking the first crosslinked polymer via a surface crosslinking agent; Provided is a superabsorbent resin that satisfies the following conditions (i) to (iii): (i) When 2 g of superabsorbent resin was added to 50 ml of artificial urine inoculated with 3000 CFU / ml of Proteus mirabilis (ATCC29906) bacteria and incubated at 35°C for 12 hours, the number of bacteria grown per unit volume of artificial urine (CFU / ml) was 10 CFU(12h): 9 below (ii) Residual monomer content measured by EDANA method WSP210.3: 450 ppm or less (iii)Hunter color B:10 or less

[0014] The present invention also provides a method for producing a hydrogel polymer comprising the steps of: cross-linking a water-soluble ethylenically unsaturated monomer having at least a partially neutralized acidic group in the presence of an internal cross-linking agent and a persulfate, followed by chopping to form a hydrogel polymer; drying and pulverizing the hydrogel polymer to form a base resin powder; and heat-treating the base resin powder in the presence of a surface cross-linking agent to cross-link the surface of the base resin powder, The persulfate is added in an amount of 1,800 to 3,500 ppm based on the total weight of the water-soluble ethylenically unsaturated monomer, The method for producing the superabsorbent resin further comprises adding a chelating agent in an amount of 6,000 to 15,000 ppm based on the total weight of the water-soluble ethylenically unsaturated monomer in at least one of the steps of crosslinking polymerization and chopping.

[0015] The present invention also provides an article, specifically a sanitary product, containing the superabsorbent polymer. Effect of the Invention

[0016] The superabsorbent polymer according to the present invention exhibits excellent antibacterial and deodorizing properties, particularly against bacteria such as Proteus mirabilis that are harmful to the human body and induce secondary malodor, and is therefore highly suitable for use in a variety of sanitary products, such as adult diapers, where secondary malodor is a particular problem.

[0017] In addition, according to the method for producing a superabsorbent resin of the present invention, it is possible to produce a superabsorbent resin that exhibits excellent water retention and pressurized water absorption capabilities due to a reduction in residual monomers in the superabsorbent resin, while also exhibiting improved bacterial growth inhibition properties and deodorizing properties, and that is also inhibited from discoloring, thereby exhibiting excellent color properties. [Brief description of the drawings]

[0018] [Figure 1] 1 is a graph showing the results of measuring the bacterial growth inhibition rate according to the amount of a chelating agent (EDTA-Na) added in Experimental Example 2. [Diagram 2] 1 is a graph showing the results of observing, by HPLC analysis, the change in the amount of a chelating agent detected in a superabsorbent resin depending on the amount of the chelating agent added during the production of the superabsorbent resin. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] The terms used in this specification are merely used to describe exemplary embodiments and are not intended to limit the present invention.

[0020] The singular expression includes the plural expression unless the context clearly indicates otherwise. It should be understood that, in this specification, the terms "comprise", "comprise", "have" and the like are intended to specify the presence of embodied features, steps, components, or combinations thereof, and do not preclude the possibility of the presence or addition of one or more other features, steps, components, or combinations thereof.

[0021] The terms first, second, third, etc. are used to describe various elements, and such terms are used only to distinguish one element from another.

[0022] Although the present invention can be modified in various ways and has various forms, specific embodiments are exemplified and described in detail below. However, it is not intended to limit the present invention to the specific disclosed embodiments, and it should be understood that the present invention includes all modifications, equivalents, and alternatives falling within the spirit and technical scope of the present invention.

[0023] The term "polymer" or "polymeric polymer" as used herein means a state in which a water-soluble ethylenically unsaturated monomer is polymerized, and may include any range of water content or particle size. Among the above polymers, a polymer having a water content (water content) of about 40% by weight or more in a state after polymerization and before drying may be called a hydrogel polymer, and particles of such a hydrogel polymer that have been crushed and dried may be called a crosslinked polymer.

[0024] In addition, the term "super absorbent resin powder" refers to a particulate material that includes a crosslinked polymer obtained by polymerizing a water-soluble ethylenically unsaturated monomer that contains acidic groups and at least a portion of the acidic groups have been neutralized, and crosslinking the polymer with an internal crosslinking agent.

[0025] In addition, the term "super absorbent polymer" refers to, depending on the context, a crosslinked polymer obtained by polymerizing a water-soluble ethylenically unsaturated monomer containing an acidic group and at least a portion of the acidic group being neutralized, or a powder-like base resin consisting of super absorbent polymer particles obtained by pulverizing the crosslinked polymer, or is used to encompass all of the crosslinked polymers or base resins that have been subjected to additional processes, such as surface crosslinking, fine powder regranulation, drying, pulverization, classification, etc., to be made into a state suitable for commercialization.

[0026] Hereinafter, the superabsorbent resin and the method for producing the same will be described in more detail with reference to specific embodiments of the invention.

[0027] Super water absorbent resin The superabsorbent resin according to the present invention is a base resin powder comprising a first crosslinked polymer of a water-soluble ethylenically unsaturated monomer having at least a partially neutralized acidic group, and a chelating agent; and a surface crosslinked layer formed on the base resin powder and including a second crosslinked polymer obtained by additionally crosslinking the first crosslinked polymer via a surface crosslinking agent; The following conditions (i) to (iii) are satisfied: (i) When 2 g of superabsorbent resin was added to 50 ml of artificial urine inoculated with 3000 CFU / ml of Proteus mirabilis (ATCC29906) bacteria and incubated at 35°C for 12 hours, the number of bacteria grown per unit volume of artificial urine (CFU / ml) was 10 CFU(12h): 9 below (ii) Residual monomer content measured by EDANA method WSP210.3: 450 ppm or less (iii) Hunter color B:10 or less.

[0028] The superabsorbent polymer was added to 50 ml of artificial urine inoculated with bacteria, specifically Proteus mirabilis (ATCC29906) at 3000 CFU / ml, and incubated at 35°C for 12 hours. The CFU(12h), which is the number of bacteria grown per unit volume of artificial urine (CFU / ml), was measured and was 1 x 10 9 More specifically, 9×10 8 or less, or 8.5 x 10 8 The smaller the number of bacteria that has been multiplied, the better the antibacterial properties. Therefore, the lower limit is not specified, but it may be 1×10 3 or more, or 1×10 6 It may be more than that.

[0029] On the other hand, the composition of the artificial urine used in the antibacterial evaluation of the superabsorbent polymer does not directly affect the antibacterial properties of the superabsorbent polymer of the present invention. Therefore, in the present invention, any artificial urine containing NaCl, urea, and a polyvalent metal can be used as the artificial urine without any particular restrictions.

[0030] As an example, in the present invention, when evaluating antibacterial properties, artificial urine containing 0.1-1.5 wt %, more specifically 0.5-1 wt %, NaCl, 0.5-5 wt %, more specifically 1-3 wt %, urea, and 0.01-0.5 wt %, more specifically 0.05-0.3 wt %, of polyvalent metals, based on the total weight of the artificial urine, can be used. In this case, the content of each component was calculated from the amount of raw material of NaCl, urea, and polyvalent metals used in the production of the artificial urine.

[0031] Meanwhile, the polyvalent metal may specifically be one or more divalent metals such as calcium and magnesium. Thus, the raw material of the polyvalent metal may be a salt (carbonate, chloride, etc.) containing the polyvalent metal or a hydrate thereof. The composition and manufacturing method of the artificial urine used in the present invention are as described in the following experimental examples.

[0032] In addition, the superabsorbent polymer according to the present invention has a RM (residual monomer) content measured by EDANA method WSP210.3 of 500 ppm or less, 400 ppm or less, or 380 ppm or less based on the total weight of the superabsorbent polymer. Since the lower the RM content, the better, the lower limit is not particularly limited, but may be 100 ppm or more, for example.

[0033] The content of RM in the superabsorbent resin can be measured by HPLC analysis, and the specific measurement method and conditions are as described in the following Experimental Examples.

[0034] The superabsorbent resins of the present invention also exhibit excellent color fastness, with the resulting Hunter color B being 10 or less, or 9 or less, or 8.7 or less, and may be 5 or more, or 6 or more, or 7 or more.

[0035] The Hunter color B of the superabsorbent resin can be measured using a color difference meter, and the specific measurement method and conditions are as described in the following experimental examples.

[0036] In addition, the superabsorbent polymer has a bacterial growth inhibition rate of 95% or more, more specifically, 99% or more, or 99.4% or more, according to the following formula 1:

[0037] [Formula 1] Bacterial growth inhibition rate = [1-{CFU(12h) / CFU control(12h)}]×100(%)

[0038] In the above formula 1, CFU(12h) indicates the number of bacteria multiplied per unit volume of artificial urine (CFU / ml) when 2g of the superabsorbent resin is added to 50ml of artificial urine inoculated with 3000CFU / ml of Proteus mirabilis (ATCC29906) bacteria and then cultured at 35°C for 12 hours, and CFU control(12h) indicates the number of bacteria multiplied per unit volume of artificial urine (CFU / ml) when artificial urine inoculated with the bacteria is cultured under the same conditions in a control superabsorbent resin, The control superabsorbent resin refers to the same superabsorbent resin as the control superabsorbent resin, except that the base resin powder does not contain a chelate.

[0039] In addition, the superabsorbent polymer exhibits excellent water absorption performance in addition to the excellent bacterial growth inhibition rate, the reduction in the residual monomer content, and the color characteristics as described above. Specifically, the superabsorbent polymer may further satisfy the following conditions (iv) to (vi): (iv) Centrifugation Retention Capacity (CRC) measured by EDENA method WSP241.3: 39 g / g or more (v) Absorbency under pressure (AUP) at 4826 Pa (0.7 psi) measured by EDANA method WSP242.3-10: 17 g / g or more (vi) The arithmetic mean of the centrifugal water retention capacity and the pressurized water absorption capacity (EFFC), expressed by the following formula 2: 28 or more

[0040] [Formula 2] EFFC=(CRC+AUP) / 2

[0041] In the above formula 2, CRC is the water retention capacity of the superabsorbent polymer in physiological saline (0.9 wt% sodium chloride aqueous solution) after centrifugation for 30 minutes, measured by EDENA method WSP241.3, AUP is the pressurized water absorption capacity of a superabsorbent polymer for one hour under 4826 Pa (0.7 psi) in physiological saline (0.9 wt % sodium chloride aqueous solution) as measured by EDANA method WSP242.3-10.

[0042] Specifically, the superabsorbent polymer has a 30-minute CRC in physiological saline (0.9 wt % sodium chloride aqueous solution) measured by EDANA method WSP241.3 of 39 g / g or more, or 40 g / g or more, and 50 g / g or less, or 45 g / g or less.

[0043] In addition, the superabsorbent polymer has an absorbency under pressure (AUP) at 4826 Pa (0.7 psi) measured by EDANA method WSP242.3-10 of 17 g / g or more, or 21 g / g or more, or 21.2 g / g or more, and 25 g / g or less, or 23 g / g or less.

[0044] Going one step further, the superabsorbent polymer has an EFFC defined by the above mathematical formula 2 of 28 or more and 32 or less, or 31.8 or less.

[0045] Since the CRC and AUP, which are in a trade-off relationship, satisfy the above-mentioned optimum range conditions, and the EFFC, which is the arithmetic mean of the CRC and AUP, also satisfies the above-mentioned range conditions, the superabsorbent resin produced by the production method of the present invention exhibits excellent water absorption performance and is suitable for application to sanitary products.

[0046] Meanwhile, the method for measuring the CRC and AUP is as described in the following experimental examples.

[0047] As described above, the highly water-absorbent polymer produced by the production method of the present invention exhibits an excellent growth inhibitory effect against Proteus mirabilis, which generates a secondary malodor by producing ammonia, and therefore can also exhibit an excellent deodorizing effect against the malodor caused by Proteus mirabilis, one of the many bacteria present on the skin, specifically, against ammonia.

[0048] Specifically, the superabsorbent resin includes a base resin powder containing a first crosslinked polymer of a water-soluble ethylenically unsaturated monomer having at least a partially neutralized acidic group and a chelating agent; and a surface crosslinked layer formed on the base resin powder and containing a second crosslinked polymer obtained by additionally crosslinking the first crosslinked polymer via a surface crosslinking agent.

[0049] Specifically, the chelating agent can be dispersed inside or on the surface of the base resin powder. More specifically, the chelating agent can be dispersed in the first crosslinked polymer in the base resin powder, or dispersed on the surface of the base resin powder. By uniformly dispersing the chelating agent in the superabsorbent resin, the superabsorbent resin can exhibit improved bacterial growth inhibition and deodorizing properties without deteriorating the physical properties of the superabsorbent resin, such as water retention and pressurized water absorption.

[0050] The chelating agent may be included in an amount of 4,500 to 12,000 ppm based on the total weight of the superabsorbent resin.

[0051] When contained within the above content range, the superabsorbent polymer exhibits sufficient antibacterial properties, and the above-described condition (i) of the superabsorbent polymer can be easily realized. More specifically, the chelating agent may be contained in an amount of 4,500 ppm or more, or 5,000 ppm or more, or 5,500 ppm or more, or 6,000 ppm or more, and 12,000 ppm or less, or 11,000 ppm or less, or 10,000 ppm or less, based on the total weight of the superabsorbent polymer.

[0052] The content of the chelating agent in the superabsorbent resin can be confirmed by HPLC analysis, the specific analysis method being as described in the following experimental examples.

[0053] The types of chelating agents will be described in detail in the following method for producing a highly water-absorbent resin.

[0054] In addition, in the superabsorbent resin according to the present invention, the base resin powder may further contain a persulfate used as a thermal polymerization initiator during preparation.

[0055] The type and amount of the persulfate used will be described in detail in the production method below.

[0056] The superabsorbent polymer according to the present invention can exhibit excellent antibacterial and deodorizing properties, particularly against bacteria such as Proteus mirabilis that are harmful to the human body and induce secondary malodor. As a result, the superabsorbent polymer can be preferably incorporated and used in various sanitary products, such as disposable diapers for children, diapers for adults, and sanitary napkins, and is particularly suitable for adult diapers, where secondary malodor caused by bacterial proliferation is a particular problem.

[0057] Manufacturing method of superabsorbent resin The method for producing a superabsorbent resin according to the present invention comprises the steps of: Step 1: cross-linking and polymerizing a water-soluble ethylenically unsaturated monomer having at least a partially neutralized acidic group in the presence of an internal cross-linking agent and a persulfate, followed by chopping to form a hydrogel polymer; drying and grinding the hydrogel polymer to form a base resin powder (Step 2); and Step 3 includes heat treating the base resin powder in the presence of a surface cross-linking agent to cross-link the surface of the base resin powder; The persulfate is added in an amount of 1,800 to 3,500 ppm based on the total weight of the water-soluble ethylenically unsaturated monomer, In one or more of the cross-linking polymerization and chopping steps, a chelating agent is added in an amount of 6,000 to 15,000 ppm based on the total weight of the water-soluble ethylenically unsaturated monomer.

[0058] When a chelating agent is introduced into a superabsorbent polymer to impart deodorizing properties, the proliferation of ammonia-producing bacteria that induce bad odors can be suppressed, but there is a problem that the residual monomer (RM) content in the superabsorbent polymer increases. If the RM content in the superabsorbent polymer is high, the basic physical properties and water absorption performance of the superabsorbent polymer decrease, making it impossible to use as a sanitary material. For this reason, a method of increasing the amount of thermal initiator added is used to reduce the RM content, but there is a problem that excess thermal initiator reduces the discoloration resistance of the superabsorbent polymer, causing it to turn yellow and deteriorating its physical properties.

[0059] In the present invention, when a superabsorbent resin having antibacterial and deodorizing properties is manufactured using a chelating agent, a persulfate (SPS) having excellent thermal initiator effect is used. Also, by simultaneously controlling the amounts of the persulfate and the chelating agent added, the content of residual monomers in the superabsorbent resin can be reduced, thereby making it possible to manufacture a superabsorbent resin having excellent water retention and pressurized water absorption capabilities, while also exhibiting improved bacterial growth inhibition and deodorizing properties, and also suppressing discoloration, thereby making it possible to manufacture a superabsorbent resin having excellent color properties.

[0060] Hereinafter, the manufacturing method according to the present invention will be described in detail step by step.

[0061] Phase 1 In the method of the present invention, step 1 is the formation of a hydrogel polymer.

[0062] Specifically, the hydrogel polymer can be prepared by cross-linking a water-soluble ethylenically unsaturated monomer having at least a partially neutralized acidic group in the presence of an internal cross-linking agent and a persulfate, chopping the resulting reaction product, and adding an optimal amount of a chelating agent during the cross-linking polymerization or chopping.

[0063] When a chelating agent is added during crosslinking polymerization, the chelating agent is uniformly dispersed in the crosslinked polymer (hereinafter referred to as the "first crosslinked polymer"), and as a result, antibacterial and deodorizing properties due to the inhibition of bacterial growth can be uniformly exhibited for a long time. In addition, the chelating agent can improve gel strength by binding with metal ions during the crosslinking polymerization stage and prevent the polymer from being oxidized by metal ions within the crosslinked structure.

[0064] On the other hand, when the chelating agent is added during chopping, the chelating agent can be added on top of the aqueous solution in which it is dissolved in water. This allows the chelating agent to be dispersed on the surface of the base resin powder, and as a result, it can be uniformly distributed in the final superabsorbent resin. This allows the antibacterial and deodorizing properties to be exhibited uniformly for a long period of time by inhibiting the growth of bacteria.

[0065] Specifically, the chelating agent may be one or more selected from the group consisting of ethylenediaminetetraacetic acid (EDTA), diethylenetriaminepentaacetic acid (DTPA), phenolic acid, citric acid, amino acid, and salts thereof. More specifically, ethylenediaminetetraacetic acid (EDTA), diethylenetriaminepentaacetic acid (DTPA) or sodium salts thereof may be used, and even more specifically, tetravalent sodium salt of ethylenediaminetetraacetic acid (EDTA) or diethylenetriaminepentaacetic acid (DTPA) may be used.

[0066] Meanwhile, unlike conventional antibacterial agents such as Ag, Zn, Cu, or tetravalent ammonium salts that destroy bacterial cell walls to kill bacteria, the chelating agent used in the present invention chelates polyvalent metals (Ca, Mg ions) necessary for bacteria to grow, thereby inhibiting only bacterial growth, thereby preventing cell deformation and the death of beneficial bacteria that may occur when bacteria die.

[0067] In particular, the chelating agent used in the present invention exhibits an excellent growth inhibitory effect against gram-negative bacteria, particularly Proteus mirabilis, which generates secondary odors by producing ammonia. As a result, the produced superabsorbent resin exhibits an excellent antibacterial effect against Proteus mirabilis, as well as a deodorizing effect against odors caused by Proteus mirabilis, specifically ammonia.

[0068] The chelating agent is added in an amount of 6,000 to 15,000 ppm based on the total weight of the water-soluble ethylenically unsaturated monomer.

[0069] If the amount of the chelating agent is less than 6,000 ppm, it is difficult to obtain sufficient antibacterial and deodorant properties, and if the amount of the chelating agent is more than 15,000 ppm, the content of RM in the superabsorbent polymer increases due to the excess chelating agent, resulting in a decrease in the physical properties and water absorption performance of the superabsorbent polymer. More specifically, the amount of the chelating agent may be 6,000 ppm or more, or 7,000 ppm or more, or 7,500 ppm or more, or 8,000 ppm or more, and 15,000 ppm or less, or 14,000 ppm or less, or 13,000 ppm or less, or 10,000 ppm or less, or 9,000 ppm or less, based on the total weight of the water-soluble ethylenically unsaturated monomer.

[0070] In addition, when considering the functions of the chelating agent and the persulfate on the physical properties and water absorption performance of the final superabsorbent resin, and on the antibacterial and deodorant properties, the effects can be further enhanced by controlling the relative mixing ratio under the condition that each content range is satisfied. Specifically, in the method for producing the superabsorbent resin according to the present invention, when a chelating agent is additionally added during crosslinking polymerization, the weight ratio of the persulfate to the chelating agent is preferably 1:3 to 1:4, or 1:3.5 to 1:4.

[0071] In addition, when a chelating agent is added during chopping, the weight ratio of the persulfate to the chelating agent is preferably 1:2 to 1:7, or 1:2.5 to 1:6.5.

[0072] When a chelating agent is added in both the cross-linking polymerization step and the chopping step, the weight ratio of the persulfate to the chelating agent is preferably 1:2 to 1:5, or 1:3 to 1:4.

[0073] The process of forming the hydrogel polymer in step 1 will be described in detail below.

[0074] In preparing the hydrogel polymer, a monomer composition in a solution state including a water-soluble ethylenically unsaturated monomer having at least a partially neutralized acidic group, a persulfate, and a solvent can be used.

[0075] In addition, when the chelating agent is added during the crosslinking polymerization process, it can be added during the preparation of the monomer composition. In this case, the monomer composition can include a water-soluble ethylenically unsaturated monomer having at least a partially neutralized acidic group, a persulfate, a solvent, and a chelating agent. The type and amount of the chelating agent are the same as those described above.

[0076] Meanwhile, the water-soluble ethylenically unsaturated monomer may be any monomer commonly used in the manufacture of superabsorbent resins. As a non-limiting example, the water-soluble ethylenically unsaturated monomer may be a compound represented by the following Chemical Formula 1:

[0077] [Chemical formula 1] R-COOM'

[0078] In the above Chemical Formula 1, R is an alkyl group having 2 to 5 carbon atoms and containing an unsaturated bond, M' is a hydrogen atom, a monovalent or divalent metal, an ammonium group or an organic amine salt.

[0079] Preferably, the monomer may be one or more selected from the group consisting of acrylic acid, methacrylic acid, and monovalent metal salts, divalent metal salts, ammonium salts, and organic amine salts of these acids. In this way, when (meth)acrylic acid and / or its salts are used as the water-soluble ethylenically unsaturated monomer, it is advantageous to obtain a highly water-absorbent resin having improved water absorption. Other examples of the monomer that can be used include maleic anhydride, fumaric acid, crotonic acid, itaconic acid, 2-acryloylethanesulfonic acid, 2-methacryloylethanesulfonic acid, 2-(meth)acryloylpropanesulfonic acid, 2-(meth)acrylamido-2-methylpropanesulfonic acid, (meth)acrylamide, N-substituted (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, polyethylene glycol (meth)acrylate, (N,N)-dimethylaminoethyl (meth)acrylate, and (N,N)-dimethylaminopropyl (meth)acrylamide.

[0080] The water-soluble ethylenically unsaturated monomer has an acidic group, and at least a portion of the acidic group can be neutralized with a neutralizing agent.

[0081] In the preparation method according to the present invention, neutralization of at least a portion of the acidic groups of the water-soluble ethylenically unsaturated monomer may be performed by adding a neutralizing agent during a process of preparing a monomer composition by mixing the water-soluble ethylenically unsaturated monomer having an acidic group, an internal crosslinking agent, sodium persulfate, and optionally a chelating agent. The monomer composition thus prepared may include a water-soluble ethylenically unsaturated monomer having an acidic group that is at least partially neutralized, an internal crosslinking agent, and sodium persulfate, and may optionally further include a chelating agent.

[0082] It is preferable that the concentration of the water-soluble ethylenically unsaturated monomer having an acidic group during the neutralization is appropriately determined in consideration of the polymerization time and reaction conditions in the subsequent polymerization reaction step. As an example, in the present invention, the concentration of the water-soluble ethylenically unsaturated monomer in a mixture containing the water-soluble ethylenically unsaturated monomer having an acidic group, an internal crosslinking agent, a polymerization initiator and a neutralizing agent may be 20 to 60% by weight, specifically, 20% by weight or more and 60% by weight or less, or 40% by weight or less.

[0083] As the neutralizing agent, one or more basic substances capable of neutralizing acidic groups, such as sodium hydroxide, potassium hydroxide, and ammonium hydroxide, can be used.

[0084] The degree of neutralization of the acidic group contained in the water-soluble ethylenically unsaturated monomer by the neutralizing agent is referred to as the neutralization degree of the water-soluble ethylenically unsaturated monomer. If the neutralization degree is too high, the neutralized monomer may precipitate and polymerization may not proceed smoothly, and conversely, if the neutralization degree is too low, the water absorption ability of the polymer may be significantly reduced and the polymer may exhibit properties similar to elastic rubber that are difficult to handle. Therefore, it is preferable that the neutralization degree of the water-soluble ethylenically unsaturated monomer is appropriately selected according to the physical properties of the superabsorbent resin to be realized. For example, in the present invention, the neutralization degree of the water-soluble ethylenically unsaturated monomer may be 50 to 90 mol%, more specifically, 50 mol% or more, 60 mol% or more, or 65 mol% or more, and 90 mol% or less, 85 mol% or less, 80 mol% or less, or 75 mol% or less.

[0085] Meanwhile, the term "internal crosslinking agent" used in the present specification is a term used to distinguish it from a "surface crosslinking agent" for crosslinking the surface of a base resin described later, and in the present invention, the internal crosslinking agent plays a role of forming a polymer having a crosslinked structure by introducing a crosslinking bond between unsaturated bonds of the water-soluble ethylenically unsaturated monomer described above.

[0086] The crosslinking in the crosslinking polymerization step is performed regardless of whether it is on the surface or inside. The surface of the superabsorbent resin particles finally produced by the surface crosslinking process of the base resin described below has a structure additionally crosslinked by a surface crosslinking agent, and the inside of the superabsorbent resin particles has a structure crosslinked by the internal crosslinking agent.

[0087] As the internal crosslinking agent, a crosslinking agent having one or more functional groups capable of reacting with the water-soluble substituent of the water-soluble ethylenically unsaturated monomer and having one or more ethylenically unsaturated groups; or a crosslinking agent having two or more functional groups capable of reacting with the water-soluble substituent of the monomer and / or the water-soluble substituent formed by hydrolysis of the monomer, can be used.

[0088] Specific examples of the internal crosslinking agent include bisacrylamide, bismethacrylamide having 8 to 12 carbon atoms, poly(meth)acrylate of polyol having 2 to 10 carbon atoms, and poly(meth)allyl ether of polyol having 2 to 10 carbon atoms. More specifically, one or more selected from the group consisting of N,N'-methylenebis(meth)acrylate, ethyleneoxy(meth)acrylate, polyethyleneoxy(meth)acrylate, polyethylene glycol diacrylate (PEGDA), polypropyleneoxy(meth)acrylate, glycerin diacrylate, glycerin triacrylate, trimethylol triacrylate, triallylamine, triaryl cyanurate, triallyl isocyanate, polyethylene glycol, diethylene glycol, and propylene glycol can be used.

[0089] Such an internal crosslinking agent can be used in an amount of 1000 to 5000 ppm based on the total weight of the water-soluble ethylenically unsaturated monomer.

[0090] If the content of the internal crosslinking agent is too low, crosslinking may not occur sufficiently, making it difficult to achieve a suitable level of strength. Also, if the content of the internal crosslinking agent is too high, the internal crosslinking density may increase, making it difficult to achieve the desired water retention. More specifically, the internal crosslinking agent may be used in an amount of 1000 ppm or more, or 1200 ppm or more, or 1400 ppm or more, and 5000 ppm or less, or 3000 ppm or less, or 2000 ppm or less, based on the total weight of the water-soluble ethylenically unsaturated monomer.

[0091] The persulfate may be sodium persulfate or potassium persulfate, and any one or a mixture of two or more of these may be used.

[0092] Among them, sodium persulfate (Na2S2O8) promotes the polymerization reaction and also causes additional polymerization reaction to proceed during the drying reaction after completion of UV polymerization, thereby preventing an increase in the RM content in the superabsorbent polymer due to the use of the chelating agent.

[0093] On the other hand, if the amount of persulfate added is excessively high, it may induce discoloration of the superabsorbent resin, so it is necessary to control the amount of persulfate added taking into account the amount of chelating agent added.

[0094] Specifically, the persulfate can be added in an amount of 1,800 to 3,500 ppm based on the total weight of the water-soluble ethylenically unsaturated monomer. If the amount of persulfate added is less than 1,800 ppm, it is difficult to sufficiently suppress the increase in RM due to the addition of a chelating agent, and if it exceeds 3,500 ppm, the excessive persulfate reduces the discoloration resistance of the superabsorbent polymer, and the Hunter color B value increases. More specifically, the persulfate can be added in an amount of 1,800 ppm or more, or 1,900 ppm or more, or 2,000 ppm or more, and 3,000 ppm or less, or 2,800 ppm or less based on the total weight of the water-soluble ethylenically unsaturated monomer.

[0095] In addition, a polymerization initiator may be further used when preparing the hydrogel polymer, that is, the polymerization initiator may be further included in the monomer composition.

[0096] The persulfate used in the production of the hydrogel polymer of the present invention can act as a thermal polymerization initiator, but an additional polymerization initiator can be further used to accelerate the polymerization reaction.

[0097] The polymerization initiator may be a thermal polymerization initiator or a photopolymerization initiator depending on the polymerization method. In addition, a certain amount of heat is generated by irradiation with ultraviolet light in the photopolymerization method, and a certain amount of heat is generated by the progress of the polymerization reaction, which is an exothermic reaction, so a thermal polymerization initiator may be additionally included.

[0098] The thermal polymerization initiator may be any known compound other than persulfates, specifically, one or more compounds selected from the group consisting of azo initiators, hydrogen peroxide, and ascorbic acid. Specifically, the azo initiator may be 2,2-azobis(2-amidinopropane) dihydrochloride, 2,2-azobis-(N,N-dimethylene)isobutyramidine dihydrochloride, 2-(carbamoylazo)isobutylonitrile, 2,2-azobis[2-(2-imidazolin-2-yl)propane]dihydrochloride, 4,4-azobis-(4-cyanovaleric acid), Examples of thermal polymerization initiators include aryl ethers such as aryl ethers, aryl ethers, and aryl ethers with aryl groups. More various thermal polymerization initiators are disclosed in "Principle of Polymerization" written by Odian (Wiley, 1981), page 203, which can be referred to.

[0099] Meanwhile, the photopolymerization initiator may be, for example, one or more compounds selected from the group consisting of benzoin ether, dialkyl acetophenone, hydroxyl alkylketone, phenyl glyoxylate, benzyl dimethyl ketal, acyl phosphine, and α-aminoketone. Meanwhile, specific examples of acylphosphine include diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, and ethyl(2,4,6-trimethylbenzoyl)phenylphosphinate. More various photoinitiators are clearly described in "UV Coatings: Basics, Recent Developments and New Application" (Elsevier, 2007), p. 115, by Reinhold Schwalm, and are not limited to the above-mentioned examples.

[0100] In general, when the concentration of the polymerization initiator is too low during the preparation of the superabsorbent resin, the polymerization rate is slowed down and a large amount of RM may be extracted into the final superabsorbent resin. Conversely, when the concentration of the polymerization initiator is too high, the polymer chain forming the network is shortened, the content of water-soluble components is increased, and the physical properties of the resin may be deteriorated, such as the decrease in water absorption capacity under pressure. In addition, in the present invention, when the hydrogel polymer is prepared, SPS is used in an amount of 1,800 to 3,500 ppm based on the total weight of the water-soluble ethylenically unsaturated monomers. In this regard, when the polymerization initiator is further used, it is preferably used in an amount of 100 to 5,000 ppm based on the total weight of the water-soluble ethylenically unsaturated monomers. Meanwhile, when the thermal polymerization initiator and the photopolymerization initiator are used simultaneously, the content means the total mixed content.

[0101] In addition, in the production method of the present invention, additives such as surfactants, thickeners, plasticizers, stabilizers, antioxidants, etc. may be further used during the production of the hydrogel polymer, i.e., the monomer composition may further contain the additives.

[0102] As an example, an anionic surfactant can be used as the surfactant. More specifically, SO3 - Compounds containing an anion, and more specifically, compounds represented by the following formula 2, can be used.

[0103] [Chemical formula 2] R-SO3Na

[0104] In the above Chemical Formula 2, R is an alkyl group having 8 to 16 carbon atoms.

[0105] The surfactant can be used in an amount of 300 ppm or less based on the total weight of the water-soluble ethylenically unsaturated monomer, and more specifically, can be used in an amount of 100 ppm or more, or 150 ppm or more and 300 ppm or less.

[0106] Furthermore, polycarboxylates can be used as the stabilizer. Specifically, 2-Propenoic acid, 2-methyl, polymer with alpha-(2-methyl-1-oxo-2-propenyl)-omega-methoxypoly(oxy-1,2-ethanediyl) and 2-Propenoic acid, graft, sodium salt (CAS No. 381686-36-8) can be used, and a corresponding product such as ACYMA-GK (manufactured by SAN NOPCO KOREA LTD) can be commercially obtained and used. The stabilizer can be used at 1500 ppm or less, more specifically, at 100 ppm or more, or 300 ppm or more, or 500 ppm or more, and 1500 ppm or less, or 1300 ppm or less, or 1000 ppm or less, or 900 ppm or less, based on the total weight of the water-soluble ethylenically unsaturated monomer.

[0107] Such a monomer composition may be prepared in the form of a solution in which the above-mentioned monomer, internal crosslinking agent, chelating agent, sodium persulfate and other additives are dissolved in a solvent.

[0108] In this case, the solvent that can be used is not limited in composition as long as it can dissolve the above-mentioned components. For example, the solvent can be water, ethanol, ethylene glycol, diethylene glycol, triethylene glycol, 1,4-butanediol, propylene glycol, ethylene glycol monobutyl ether, propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, methyl ethyl ketone, acetone, methyl amyl ketone, cyclohexanone, cyclopentanone, diethylene glycol monomethyl ether, diethylene glycol ethyl ether, toluene, xylene, butyrolactone, carbitol, methyl cellosolve acetate, N,N-dimethylacetamide, or a mixture thereof.

[0109] The solvent may be included in an amount remaining after excluding the above-mentioned components based on the total content of the monomer composition.

[0110] In addition, the formation of the hydrogel polymer by polymerization of the monomer composition may be performed by a conventional polymerization method, and the process is not particularly limited. For example, the polymerization method is largely divided into thermal polymerization and photopolymerization depending on the type of polymerization energy source, and the thermal polymerization may be performed in a reactor having a stirring shaft such as a kneader, and the photopolymerization may be performed in a reactor equipped with a movable conveyor belt.

[0111] As an example, the monomer composition is introduced into a reactor such as a kneader equipped with an agitator shaft, and hot air is supplied thereto or the reactor is heated to thermally polymerize the monomer composition, thereby obtaining a hydrogel polymer. At this time, depending on the type of the agitator shaft equipped in the reactor, the hydrogel polymer discharged from the outlet of the reactor is obtained as particles of several millimeters to several centimeters in size. Specifically, the obtained hydrogel polymer is obtained in various forms depending on the concentration of the monomer composition injected and the injection speed, and generally, a hydrogel polymer having a weight average particle size of 2 to 50 mm is obtained.

[0112] As another example, when the photopolymerization of the monomer composition is carried out in a reactor equipped with a movable conveyor belt, a sheet-like hydrogel polymer is obtained. In this case, the thickness of the sheet may vary depending on the concentration and injection speed of the monomer composition to be injected, but it is generally preferable to adjust the thickness to 0.5 to 5 cm in order to ensure the production speed while allowing the entire sheet to be polymerized uniformly.

[0113] After the cross-linking polymerization is completed, the resulting polymerization reaction product is subjected to a chopping step.

[0114] The chopping step is different from the grinding step carried out after the subsequent drying step in that the chopping step is carried out while the crosslinked polymer obtained as a result of the crosslinking polymerization is in a wet state before drying.

[0115] In addition, in the present invention, a chelating agent may be additionally added during chopping of the crosslinked polymer, with the type, method and amount of the chelating agent being the same as described above.

[0116] The chopping may be performed by a conventional chopping method, such as using a chopping device, except that a chelating agent is added. In the present invention, the chopping process for the crosslinked polymer may be performed using a chopper, since it is easy to add a chelating agent and the crosslinked polymer and the chelating agent can be mixed homogeneously.

[0117] The water content of the hydrogel polymer prepared by this method may be 40 to 80% by weight. Meanwhile, the "water content" refers to the water content relative to the total weight of the hydrogel polymer, and means the weight of the hydrogel polymer minus the weight of the polymer in a dry state. Specifically, it is defined as a value calculated by measuring the weight loss due to the evaporation of water in the polymer during the process of drying by increasing the temperature of the polymer by infrared heating. At this time, the drying conditions are from room temperature to about 180°C, and the water content is measured while maintaining the temperature for about 40 minutes.

[0118] In the method according to the present invention, when a chelating agent is added during the crosslinking polymerization step, the hydrogel polymer produced is a crosslinked polymer obtained by crosslinking a water-soluble ethylenically unsaturated monomer containing an acidic group and at least a portion of the acidic group being neutralized in the presence of an internal crosslinking agent, a persulfate, and optionally a chelating agent. As a result, the hydrogel polymer has a three-dimensional network structure in which the main chain formed by polymerization of the monomer is crosslinked by the internal crosslinking agent, and the chelating agent is uniformly dispersed and distributed in the crosslinked polymer, specifically, in the interior and on the surface of the three-dimensional network structure of the crosslinked polymer.

[0119] Furthermore, when the chelating agent is added during the chopping process, the hydrogel polymer has a three-dimensional network structure in which a main chain formed by polymerization of a water-soluble ethylenically unsaturated monomer containing the acidic groups and at least a portion of the acidic groups being neutralized is crosslinked by the internal crosslinking agent, and the chelating agent is uniformly dispersed and distributed on the surface of the base resin powder containing the hydrogel polymer.

[0120] Furthermore, when the chelating agent is added in both the cross-linking polymerization step and the chopping step, the chelating agent is uniformly dispersed and distributed not only in the cross-linked polymer in the hydrogel polymer but also on the surface of the base resin powder containing the hydrogel polymer.

[0121] In this way, when the hydrogel polymer has a three-dimensional network structure, the water retention capacity and water absorption capacity under pressure, which are various physical properties of the superabsorbent resin, can be significantly improved compared to when the hydrogel polymer has a two-dimensional linear structure that is not additionally crosslinked by an internal crosslinking agent. In addition, the chelating agent that is uniformly dispersed in the crosslinked polymer or hydrogel polymer can uniformly exhibit excellent antibacterial and deodorizing properties for a long period of time.

[0122] Phase 2 In the method according to the present invention, step 2 is a step of drying and pulverizing the hydrogel polymer prepared in step 1 to form a base resin powder.

[0123] The drying step is not particularly limited, and a conventional drying method used for drying a hydrogel polymer can be used, such as hot air supply, infrared radiation, ultrashort wave radiation, or ultraviolet radiation.

[0124] If the drying temperature during the drying is too low, the drying time will be long, and the physical properties of the superabsorbent resin produced in the end may be deteriorated, and conversely, if the drying temperature is too high, only the surface of the polymer will be dried, and fine powder may be generated in the subsequent pulverization step, or the physical properties of the superabsorbent resin may be deteriorated. Therefore, in the present invention, the drying step of the hydrogel polymer is performed in the temperature range of 150 to 250°C. More specifically, it may be performed at a temperature of 150°C or higher, or 160°C or higher, and 200°C or lower, or 180°C or lower.

[0125] The drying time can be appropriately determined depending on the drying temperature. For example, in the present invention, the drying time may be 20 to 90 minutes, taking into consideration the water content of the produced hydrogel polymer, the drying temperature conditions, and the process efficiency therewith.

[0126] After the drying step under such conditions, the water content of the obtained polymer may be 0.1 to 10% by weight based on the total weight of the dried polymer. That is, the drying method, drying temperature and drying time can be appropriately selected within the above-mentioned ranges so that the water content of the dried polymer is 0.1 to 10% by weight.

[0127] Meanwhile, the method according to the present invention may further include a step of roughly pulverizing the dried hydrogel polymer after the drying step and before the pulverizing step in order to increase pulverization efficiency.

[0128] The dried hydrogel polymer may be coarsely pulverized using a conventional pulverizer, etc. In this case, the pulverizer that can be used is not particularly limited, and specifically, a vertical pulverizer, a turbo cutter, a turbo grinder, a rotary cutter mill, a cutter mill, a disc mill, a shred crusher, a crusher, a chopper, or a disc cutter can be used.

[0129] Next, after the drying step or after the coarse pulverization step, a pulverization step is carried out.

[0130] The pulverization may be performed so that the particle size of the polymer powder obtained after the pulverization step is 150 to 850 μm. Specifically, the pulverizer used for pulverizing to have such a particle size may be a pin mill, a hammer mill, a screw mill, a roll mill, a disc mill, a jog mill, or the like.

[0131] In order to control the physical properties of the highly water-absorbent resin powder that is made into a final product after such a pulverization step, a classification step may be carried out in which the polymer powder obtained after pulverization is classified according to particle size.

[0132] By such a classification step, fine powders having a particle size of less than 150 μm and coarse particles having a particle size of more than 850 μm can be separated and removed to obtain base resin particles having a size of 150 to 850 μm. In addition, during the classification step, the polymer powder may be classified so as to have a certain weight ratio according to the particle size range.

[0133] The classification step may be carried out by a conventional method, such as using standard sieves according to ASTM regulations.

[0134] The crosslinked polymer obtained by crosslinking the water-soluble ethylenically unsaturated monomer through the internal crosslinking agent in the above-mentioned process is dried, pulverized and classified into particles or powder, which is called base resin. Specifically, the base resin powder may be in the form of a fine powder having a particle size of 150 to 850 μm.

[0135] The base resin produced by the process according to the present invention has a water retention capacity (CRC) measured by EDANA method WSP241.3 of 50 g / g or more, or 55 g / g or more, and 60 g / g or less, or 58 g / g or less.

[0136] Generally, the water retention capacity (CRC) of the base resin inevitably decreases during the surface cross-linking reaction step described below. However, in the present invention, the water retention capacity of the base resin is made high, so that the water retention capacity of the final superabsorbent resin can be maintained high.

[0137] In addition, the content of RM in the base resin is 500 ppm or less, or 480 ppm, based on the total weight of the base resin, which is lower than that of base resins produced by conventional methods for producing superabsorbent resins, and this allows the RM content in the final superabsorbent resin to be kept low.

[0138] Furthermore, the method according to the present invention may further include a step of mixing the base resin powder with a regranulated fine powder prior to carrying out the surface cross-linking process after the preparation of the base resin powder.

[0139] In general, fine powder is inevitably generated during the process of crushing and classifying after drying during the production of superabsorbent polymer. Therefore, in all commercial processes, the generated fine powder is granulated with water to increase the particle size and recycled in the form of fine powder regranulated material. Therefore, in the present invention, fine powder generated during the process of producing superabsorbent polymer, particularly the crushing and classifying process after drying of the hydrogel polymer, is regranulated by adding water to the fine powder regranulated material, which can be added to the base resin powder and used, or can be obtained commercially and used.

[0140] The regranulated fine powder may be mixed in an amount of 20 to 40 parts by weight based on 100 parts by weight of the base resin powder. If the amount of the regranulated fine powder mixed is excessively large beyond the above range, the physical properties of the final superabsorbent resin may be deteriorated.

[0141] Phase 3 In the preparation method according to the present invention, step 3 is a step of heat treating the base resin powder prepared in step 2 in the presence of a surface cross-linking agent to cross-link the surface of the base resin powder to form a surface cross-linked layer.

[0142] The surface cross-linking is intended to increase the cross-linking density near the surface of the base resin powder relative to the cross-linking density inside the particle. In general, the surface cross-linking agent is applied to the surface of the base resin powder. Thus, this reaction occurs on the surface of the base resin powder, which improves the cross-linking on the surface of the particle without substantially affecting the inside of the particle. Thus, the surface cross-linked base resin powder has a higher degree of cross-linking near the surface than inside, and as a result, it can exhibit improved water absorption capacity under pressure compared to the case where the surface cross-linked layer is not formed. On the other hand, when the surface cross-linked layer is not formed, the gel strength can be increased to improve the water absorption capacity under pressure. However, when a superabsorbent resin with an increased gel strength without forming a surface cross-linked layer is applied to an absorbent article, when pressure is applied to the gel, the gel breaks and the microorganisms absorbed in the absorbent article are exposed to the outside, which may cause secondary contamination. However, when the surface cross-linked layer is formed as described above, the gel shape is well maintained even when pressure is applied to the gel, thereby preventing the microorganisms absorbed during use from being exposed to the outside.

[0143] Specifically, the surface crosslinking can be carried out using a surface crosslinking solution containing a surface crosslinking agent and a water solvent.

[0144] The surface cross-linking agent is not limited in its constitution as long as it is a compound capable of reacting with the functional group of the polymer.Preferably, in order to improve the properties of the resulting superabsorbent resin, the surface cross-linking agent may be one or more selected from the group consisting of polyhydric alcohol compounds, epoxy compounds, polyamine compounds, haloepoxy compounds, condensation products of haloepoxy compounds, oxazoline compounds, mono-, di- or polyoxazolidinone compounds, cyclic urea compounds, polyvalent metal salts, and alkylene carbonate compounds.

[0145] Specifically, examples of polyhydric alcohol compounds that can be used include one or more selected from the group consisting of ethylene glycol, propylene glycol, 1,3-propanediol, 1,4-butanediol, 1,6-hexanediol, 1,2-hexanediol, 1,3-hexanediol, 2-methyl-1,3-propanediol, 2,5-hexanediol, 2-methyl-1,3-pentanediol, 2-methyl-2,4-pentanediol, tripropylene glycol, and glycerol.

[0146] In addition, as the epoxy compound, ethylene glycol diglycidyl epoxide, ethylene glycol diglycidyl ether, glycidol, etc. can be used, and as the polyamine compound, one or more selected from the group consisting of ethylenediamine, diethylenetriamine, triethylenetetraamine, tetraethylenepentamine, pentaethylenehexamine, polyethyleneimine, and polyamidepolyamine can be used.

[0147] As the haloepoxy compound, epichlorohydrin, epibromohydrin, and α-methylepichlorohydrin can be used, while as the mono-, di-, or polyoxazolidinone compound, for example, 2-oxazolidinone can be used.

[0148] The alkylene carbonate compound may be an alkylene carbonate having 2 to 6 carbon atoms, such as ethylene carbonate or propylene carbonate. These may be used alone, or two or more alkylene carbonates having different carbon numbers may be mixed and used. An example is a mixture of ethylene carbonate and propylene carbonate. The ethylene carbonate and propylene carbonate may be mixed and used in a weight ratio of 2:8 to 8:2, 4:6 to 6:4, or 4.5:5.5 to 5.5:4.5.

[0149] As the polyvalent metal salt, specifically, sulfates or carboxylates containing a metal such as aluminum can be used, and among them, aluminum sulfate is more preferably used.

[0150] The surface cross-linking agent may be added in an amount of 0.001 to 5 parts by weight relative to 100 parts by weight of the base resin powder. For example, the surface cross-linking agent may be used in an amount of 0.001 parts by weight or more, or 0.005 parts by weight or more, or 0.01 parts by weight or more, or 0.1 parts by weight or more and 5 parts by weight or less, or 3 parts by weight or less, or 2 parts by weight or less, or 1 part by weight or less relative to 100 parts by weight of the base resin powder. By adjusting the content range of the surface cross-linking agent within the above-mentioned range, a highly water-absorbent resin exhibiting various physical properties such as excellent water absorption performance and liquid permeability can be produced. If the content of the surface cross-linking agent is too low, the surface cross-linking reaction hardly occurs, and if the content exceeds 5 parts by weight relative to 100 parts by weight of the base resin powder, the excessive progress of the surface cross-linking reaction may cause a decrease in water absorption capacity and physical properties.

[0151] There is no limitation on the constitution of the method for mixing the surface crosslinking agent with the base resin powder. A method of mixing the surface crosslinking agent and the base resin powder in a reaction tank, a method of spraying the surface crosslinking agent onto the base resin powder, a method of continuously supplying the base resin powder and the surface crosslinking agent to a continuously operating mixer, and the like can be used.

[0152] In addition to the surface crosslinking agent, water and alcohol may be mixed together and added in the form of the surface crosslinking solution. When water and alcohol are added, there is an advantage that the surface crosslinking agent can be uniformly dispersed in the base resin powder. At this time, the content of the added water and alcohol is preferably 5 to 12 parts by weight per 100 parts by weight of the polymer in order to induce uniform dispersion of the surface crosslinking agent, prevent the agglomeration of the base resin powder, and at the same time, optimize the surface penetration depth of the crosslinking agent.

[0153] In addition to the above components, the surface cross-linking solution may further include one or more of a fluidizing agent, a discoloration inhibitor, a reducing agent, an inorganic filler, aluminum sulfate, and a thickener.

[0154] The fluidizer acts as a lubricant and plays a role in improving the mixing stability and uniformity during the preparation of the surface crosslinking solution. Generally, the permeability among the physical properties of a superabsorbent resin is in a trade-off relationship with the water retention capacity and the water absorption capacity under pressure, but when the polycarboxylic acid copolymer is added, it is possible to provide a superabsorbent resin having excellent water absorption properties such as the water retention capacity and the water absorption capacity under pressure, and also having improved permeability.

[0155] Specific examples of the fluidizing agent include polycarboxylic acid copolymers and polycarboxylates, and any one or a mixture of two or more of these can be used.

[0156] Specifically, the polycarboxylic acid copolymer may contain at least one of a repeating unit represented by the following chemical formula 3-a and a repeating unit represented by the following chemical formula 3-b.

[0157] [ka]

[0158] In the above chemical formulas 3-a and 3-b, R 1 , R 2 and R3 are each independently a hydrogen atom or an alkyl group having 1 to 6 carbon atoms, RO is an oxyalkylene group having 2 to 4 carbon atoms; M 1 is hydrogen or a monovalent metal or nonmetal ion, X is -COO-, an alkyloxy group having 1 to 5 carbon atoms, or an alkyldioxy group having 1 to 5 carbon atoms; m is an integer from 1 to 100; n is an integer from 1 to 1000, p is an integer of 1 to 150, and when p is 2 or more, -RO- repeated 2 or more times may be the same or different.

[0159] Here, the polycarboxylic acid-based copolymer may include one or more repeating units having structures different from each other among the repeating units represented by the chemical formula 3-a; one or more repeating units having structures different from each other among the repeating units represented by the chemical formula 3-b; or a repeating unit represented by the chemical formula 3-a and a repeating unit represented by the chemical formula 3-b.

[0160] More specifically, the polycarboxylic acid copolymer may be a copolymer containing a repeating unit derived from an alkoxypolyalkylene glycol mono(meth)acrylic acid ester monomer (a representative example is methoxypolyethylene glycol monomethacrylate (MPEGMAA)); and (meth)acrylic acid or an ester monomer thereof (a representative example is (meth)acrylic acid), and more specifically, a copolymer containing a repeating unit derived from methoxypolyethylene glycol monomethacrylate and a repeating unit derived from (meth)acrylic acid, or a random copolymer containing a repeating unit derived from methoxypolyethylene glycol monomethacrylate and a repeating unit derived from (meth)acrylic acid, which may be used to exhibit the above-mentioned effects.

[0161] In addition, in order to better exhibit the effect of the addition of the polycarboxylic acid copolymer, the polycarboxylic acid copolymer preferably has a weight average molecular weight of 500 to 1,000,000 g / mol, more specifically, 500 g / mol or more, or 5,000 g / mol or more, or 10,000 g / mol or more, or 35,0000 g / mol or more, or 40,000 g / mol or more, and 1,000,000 g / mol or less, or 800,000 g / mol or less, or 500,000 g / mol or less, or 100,000 g / mol or less, or 60,000 g / mol or less. If the molecular weight of the polycarboxylic acid copolymer is less than 500 g / mol, the lubricating effect may be reduced, and if it exceeds 1,000,000 g / mol, the solubility in water may be reduced.

[0162] Meanwhile, in the present invention, the weight average molecular weight (Mw) of the polycarboxylic acid copolymer can be measured using gel permeation chromatography. Specifically, a Waters PL-GPC220 instrument was used as the gel permeation chromatography (GPC) device, and a Polymer Laboratories PLgel MIX-B column (length 300 mm) was used. At this time, the measurement temperature was 160°C, 1,2,4-trichlorobenzene was used as the solvent, and the flow rate was 1mL / min. 10 mg of the polycarboxylic acid copolymer sample was pretreated by dissolving it in 1,2,4-trichlorobenzene containing 0.0125% BHT at 160°C for 10 hours using a sample pretreatment system PL-SP260 (Agilent Technology), and the concentration was adjusted to 10 mg / 10 mL, and then supplied in an amount of 200 μL. The Mw value was derived using a calibration curve formed using a polystyrene standard test piece. Nine types of polystyrene standard test pieces were used, with weight average molecular weights of 2,000 g / mol, 10,000 g / mol, 30,000 g / mol, 70,000 g / mol, 200,000 g / mol, 700,000 g / mol, 2,000,000 g / mol, 4,000,000 g / mol, and 10,000,000 g / mol.

[0163] Further, specific examples of the polycarboxylate include 2-propenoic acid, 2-methyl, polymer with alpha-(2-methyl-1-oxo-2-propenyl)-omega-methoxypoly(oxy-1,2-ethanediyl) and 2-propenoic acid, graft, sodium salt (CAS No. 381686-36-8), and the like. Also, a commercially available product such as ACYMA-GK (manufactured by SAN NOPCO KOREA LTD.) corresponding thereto may be used.

[0164] The flow agent can be used in an amount of 1 part by weight or less, based on 100 parts by weight of the base resin powder, more specifically, an amount of 0.001 parts by weight or more, or 0.03 parts by weight or more, or 0.05 parts by weight or more and 1 part by weight or less, or 0.5 parts by weight or less, or 0.1 parts by weight or less.

[0165] The discoloration inhibitor may include sulfonic acid derivatives such as disodium alpha-sulfoglycolate; phosphonic acid derivatives such as lauryl phosphonic acid or stearyl phosphonic acid; and the like. TM A commercially available product such as HP (manufactured by L. Brugemann KG) may also be included. The discoloration inhibitor may be included in an amount of 0.01 to 0.2 parts by weight based on 100 parts by weight of the base resin powder, and more specifically, the amount may be 0.01 part by weight or more, or 0.03 part by weight or more, or 0.05 part by weight or more and 0.2 part by weight or less, or 0.1 part by weight or less, or 0.08 part by weight or less.

[0166] The reducing agent may include sodium bisulfite, sodium metabisulfite (Na2S2O5), sodium hydrosulfite, sodium thiosulfate, or sodium formaldehyde sulfoxylate. The reducing agent may be included in an amount of 0.01 to 0.2 parts by weight based on 100 parts by weight of the base resin powder. More specifically, the reducing agent may be included in an amount of 0.01 parts by weight or more, or 0.03 parts by weight or more, or 0.05 parts by weight or more, and 0.2 parts by weight or less, or 0.1 parts by weight or less, or 0.08 parts by weight or less, based on 100 parts by weight of the base resin powder.

[0167] The inorganic filler may include silica, clay, alumina, silica-alumina composite, titania, zinc oxide, or silicate. The inorganic filler may be included in an amount of 0.01 to 0.5 parts by weight based on 100 parts by weight of the base resin powder. More specifically, the inorganic filler may be included in an amount of 0.01 parts by weight or more and 0.5 parts by weight or less, or 0.3 parts by weight or less, or 0.1 parts by weight or less, based on 100 parts by weight of the base resin powder.

[0168] The surface cross-linking solution may contain aluminum sulfate. The aluminum sulfate may be contained in an amount of 0.01 to 2 parts by weight based on 100 parts by weight of the base resin powder. More specifically, the aluminum sulfate may be contained in an amount of 0.01 parts by weight or more, or 0.1 parts by weight or more, or 0.15 parts by weight or more and 2.0 parts by weight or less, or 1 part by weight or less, or 0.5 parts by weight or less based on 100 parts by weight of the base resin powder.

[0169] In addition, the surface cross-linking solution may further include a thickener. By additionally cross-linking the surface of the base resin powder in the presence of the thickener, the deterioration of physical properties after pulverization may be minimized. Specifically, the thickener may be one or more selected from polysaccharides and hydroxy-containing polymers. As the polysaccharide, a gum-based thickener, a cellulose-based thickener, etc. may be used. Specific examples of the gum-based thickener include xanthan gum, gum arabic, karaya gum, tragacanth gum, ghatti gum, guar gum, locust bean gum, and psyllium seed gum, while specific examples of the cellulose-based thickener include hydroxypropylmethylcellulose, carboxymethylcellulose, methylcellulose, hydroxymethylcellulose, hydroxyethylcellulose, hydroxypropylcellulose, hydroxyethylmethylcellulose, hydroxymethylpropylcellulose, hydroxyethylhydroxypropylcellulose, ethylhydroxyethylcellulose, and methylhydroxypropylcellulose. On the other hand, specific examples of the hydroxy-containing polymer include polyethylene glycol and polyvinyl alcohol.

[0170] In addition, the surface cross-linking reaction may be carried out by heating the base resin powder to which the surface cross-linking agent has been added at a temperature of 120 to 220°C for 60 to 120 minutes. If the cross-linking reaction temperature is less than 120°C, the surface cross-linking reaction may not occur sufficiently, and if it exceeds 220°C, the surface cross-linking reaction may occur excessively. Furthermore, if the cross-linking reaction time is too short, less than 60 minutes, the cross-linking reaction may not occur sufficiently, and if the cross-linking reaction time exceeds 120 minutes, the cross-linking density of the particle surface may be excessively high due to the excessive surface cross-linking reaction, resulting in a decrease in physical properties. More specifically, the surface cross-linking step may be carried out by heating at a temperature of 120°C or more, or 180°C or more and 220°C or less, or 190°C or less, for 60 minutes or more, or 80 minutes or more and 120 minutes or less, or 90 minutes or less. More specifically, the surface cross-linking step may be carried out at 180 to 190°C for 80 to 90 minutes.

[0171] The temperature raising means for the surface crosslinking reaction is not particularly limited. Heating can be performed by supplying a heat medium or directly supplying a heat source. At this time, the type of heat medium that can be used can be a heated fluid such as steam, hot air, hot oil, etc., but the present invention is not limited to these, and the temperature of the heat medium to be supplied can be appropriately selected in consideration of the means of the heat medium, the heating rate, and the target temperature of the heat raising. On the other hand, examples of the heat source to be directly supplied include heating by electricity and heating by gas, but the present invention is not limited to the above examples.

[0172] By the above-mentioned production process, a surface cross-linked layer is formed on the surface of the base resin powder.

[0173] The production method according to the present invention may further include a classification step after the surface crosslinking.

[0174] The classification step may be carried out using a standard mesh according to the ASTM standard, and as a result, a highly water-absorbent resin having a particle size of 150 to 850 μm can be obtained.

[0175] Specifically, 95% by weight or more, 97% by weight or more, or 99% by weight or more of the superabsorbent polymer have a particle size of 150 μm to 850 μm. The superabsorbent polymer may contain 50% by weight or more of particles having a particle size of 300 μm to 600 μm. Furthermore, the superabsorbent polymer may contain 3% by weight or less, or less than 3% by weight of fine powder having a particle size of less than 150 μm.

[0176] In addition, the superabsorbent resin produced by the method of the present invention includes a base resin powder including a first crosslinked polymer of a water-soluble ethylenically unsaturated monomer having at least a partially neutralized acidic group, a persulfate, and a chelating agent; and a surface crosslinked layer formed on the base resin powder and including a second crosslinked polymer in which the first crosslinked polymer is additionally crosslinked via a surface crosslinking agent. The chelating agent may be present in a dispersed state in the crosslinked polymer or dispersed on the surface of the first crosslinked polymer or the base resin powder. By uniformly dispersing the chelating agent in the superabsorbent resin, the superabsorbent resin can exhibit improved bacterial growth inhibition and deodorizing properties without deteriorating the physical properties of the superabsorbent resin, such as water retention and pressurized water absorption.

[0177] Thus, according to the present invention, there are provided articles containing the superabsorbent polymer, specifically sanitary products such as diapers and sanitary napkins.

[0178] Such a sanitary product can have the same structure as a normal sanitary product, except that the highly water-absorbent polymer of one embodiment is contained in the absorbent body.

[0179] The functions and effects of the present invention will be described in more detail below with reference to specific examples of the present invention, however, these examples are merely presented as examples of the present invention and do not define the scope of the invention.

[0180] <Production of superabsorbent resin> Example 1-1 In a 3L glass container equipped with a stirrer, nitrogen injector, and thermometer, 438.5g of acrylic acid monomer was put into the container, and 1440ppm of polyethylene glycol diacrylate (PEGDA, Mn=400g / mol) as an internal crosslinking agent, 80ppm of bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide as a photopolymerization initiator, 2000ppm of sodium persulfate (SPS), 8000ppm of EDTA, 900ppm of an aqueous solution (concentration 50%) of ACYMA-GK (manufactured by SAN NOPCO KOREA LTD.) as a polycarboxylic acid stabilizer, and 98% sodium hydroxide solution were mixed to prepare a monomer composition (total weight basis solid content (TSC) of the monomer composition=43.3% by weight, neutralization degree=72%).

[0181] The monomer composition was placed in a stainless steel container measuring 250 mm in width, 250 mm in length, and 30 mm in height, and then irradiated with ultraviolet light for 60 seconds in a UV chamber at 80°C to cause a crosslinking polymerization reaction (irradiation dose: 10 mV / cm 2 The resulting crosslinked polymer was cut into pieces of about 5 cm x 5 cm size, and then chopped in a chopper to obtain a hydrogel polymer.

[0182] The obtained hydrous gel polymer was dried in a hot air oven at 185°C for 35 minutes, pulverized, and then classified using a standard mesh sieve according to ASTM standards to obtain a base resin (BR) powder having a particle size of 150 to 850 μm (particle size of base resin powder: #20 / #30 / #50 / #100 / Pan=0 / 19 / 64 / 16 / 1 (wt%)).

[0183] 100 parts by weight of the obtained base resin powder was mixed with 33 parts by weight of fine powder regranulated material (CRC42, particle size: #20 / #30 / #50 / #100 / Pan=0 / 19 / 64 / 16 / 1 (wt%)) produced by regranulating, together with water, fine powder having a particle size of less than 150 μm generated during the drying, pulverizing and classifying processes for the hydrogel polymer.

[0184] The mixed powder of the base resin powder and the regranulated fine powder produced above was placed in a surface crosslinking mixer, and then a surface crosslinking agent in the form of a solution produced by mixing 4.96 parts by weight of water, 0.5 parts by weight of a mixture of ethylene carbonate (EC) and propylene carbonate (PC) (weight ratio of EC:PC=1:1), 0.05 parts by weight of ACYMA-GK (manufactured by SAN NOPCO KOREA LTD., aqueous solution with a concentration of 50%), and 0.405 parts by weight of an aqueous aluminum sulfate solution (concentration of 35%) based on 100 parts by weight of the base resin powder was added, and the mixture was mixed at a speed of 500 rpm for 30 seconds.

[0185] The resulting mixture was transferred to a jacket-type cylindrical surface reactor equipped with an agitator, and then a surface cross-linking reaction was carried out. The surface cross-linking reaction was carried out until the final superabsorbent resin reached a target CRC value of 40 g / g, and the surface cross-linking reaction time was confirmed after completion of the surface cross-linking reaction. In addition, during the surface cross-linking reaction, the temperature in the reactor was raised to a profile of 184°C after 40 minutes, 181°C after 60 minutes, and 181°C after 80 minutes, based on the start of the surface cross-linking reaction, and thereafter, the surface cross-linking reaction was carried out at 181°C for an additional 10 minutes.

[0186] Thereafter, the surface-treated powder was classified using a standard mesh sieve according to ASTM standards to obtain a highly water-absorbent resin powder having a particle size of 150 to 850 μm.

[0187] Comparative Examples 1-1 to 1-3 A highly water-absorbent resin powder was produced in the same manner as in Example 1-1, except that the conditions shown in Table 1 below were used.

[0188] Example 2-1 438.5 g of acrylic acid monomer was put into a 3 L glass vessel equipped with a stirrer, nitrogen injector, and thermometer, and 1600 ppm of polyethylene glycol diacrylate (PEGDA, Mn=400 g / mol) as an internal crosslinking agent based on the total weight of the acrylic acid, 80 ppm of bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide as a photoinitiator, 2000 ppm of sodium persulfate (SPS), and 98% sodium hydroxide solution were mixed to prepare a monomer composition (total weight based solid content (TSC) of the monomer composition=41% by weight, neutralization degree=72%).

[0189] The monomer composition was placed in a stainless steel container measuring 250 mm in width, 250 mm in length, and 30 mm in height, and then irradiated with ultraviolet light for 60 seconds in a UV chamber at 80° C. to cause a crosslinking polymerization reaction (irradiation dose: 10 mV / cm 2 ) and aging for 2 minutes to obtain a crosslinked polymer. The obtained crosslinked polymer was cut into a size of about 5 cm x 5 cm, and then chopped in a chopper to obtain a hydrogel polymer. During the chopping, an aqueous solution of EDTA-4Na (concentration: 40%) was added in an amount of 8000 ppm of EDTA-4Na based on the total weight of the acrylic acid monomer.

[0190] The resulting hydrous gel polymer was dried in a hot air oven at 185°C for 35 minutes, pulverized, and then classified using a standard ASTM mesh sieve to obtain a base resin (BR) powder having a particle size of 150 to 850 μm (particle size of base resin powder: #20 / #30 / #50 / #100 / Pan=0 / 19 / 64 / 16 / 1 (wt%)).

[0191] 100 parts by weight of the obtained base resin powder was mixed with 33 parts by weight of fine powder regranulated material (CRC42, particle size: #20 / #30 / #50 / #100 / Pan=0 / 19 / 64 / 16 / 1 (wt%)) prepared by regranulating fine powder having a particle size of less than 150 μm generated during the drying and pulverizing process with water.

[0192] To the mixed powder of the base resin powder and regranulated fine powder produced above, a surface crosslinking solution produced by mixing 4.7 parts by weight of water, 0.2 parts by weight of ethylene carbonate, 0.05 parts by weight of ACYMA-GK (manufactured by SAN NOPCO KOREA LTD., aqueous solution with a concentration of 50%), and 0.35 parts by weight of an aqueous aluminum sulfate solution (concentration of 35%) based on 100 parts by weight of the base resin powder was added, and the mixture was mixed at a speed of 500 rpm for 30 seconds.

[0193] The resulting mixture was transferred to a jacket-type cylindrical surface reactor equipped with an agitator, and then a surface cross-linking reaction was carried out. The surface cross-linking reaction was carried out until the final superabsorbent resin reached a target CRC value of 40 g / g, and the surface cross-linking reaction time was confirmed after completion of the surface cross-linking reaction. In addition, during the surface cross-linking reaction, the temperature in the reactor was raised to a profile of 184°C after 40 minutes, 181°C after 60 minutes, and 181°C after 80 minutes, based on the start of the surface cross-linking reaction, and thereafter, the surface cross-linking reaction was carried out at 181°C for an additional 10 minutes.

[0194] Thereafter, the surface-treated powder was classified using a standard mesh sieve according to ASTM standards to obtain a highly water-absorbent resin powder having a particle size of 150 to 850 μm.

[0195] Comparative Examples 2-1 to 2-3 A highly water-absorbent resin was produced in the same manner as in Example 2-1, except that the crosslinking polymerization and surface crosslinking reaction were carried out under the conditions shown in Table 2 below.

[0196] Example 2-2, Example 2-3 and Comparative Example 2-4 A surface crosslinking solution was prepared by mixing 4.96 parts by weight of water, 0.5 parts by weight of a mixture of ethylene carbonate and propylene carbonate (weight ratio of EC:PC=1:1), 0.05 parts by weight of an aqueous solution of ACYMA-GK (manufactured by SAN NOPCO KOREA LTD.) (concentration 50%), and 0.405 parts by weight of an aqueous solution of aluminum sulfate (concentration 35%) based on 100 parts by weight of a base resin powder, and a superabsorbent resin was prepared in the same manner as in Example 2-1, except that the polymerization and surface crosslinking reactions were carried out under the conditions shown in Table 2 below.

[0197] Example 3 In a 3L glass container equipped with a stirrer, nitrogen injector, and thermometer, 438.5g of acrylic acid monomer was put, and 1600ppm of polyethylene glycol diacrylate (PEGDA, Mn=400g / mol) as an internal crosslinking agent based on the total weight of the acrylic acid, 80ppm of bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide as a photopolymerization initiator, 2000ppm of sodium persulfate (SPS), 4000ppm of EDTA, 900ppm of an aqueous solution (concentration 50%) of ACYMA-GK (manufactured by SAN NOPCO KOREA LTD.) as a polycarboxylic acid stabilizer, and 98% sodium hydroxide solution were mixed to prepare a monomer composition (total weight based solid content (TSC) of the monomer composition=41% by weight, neutralization degree=72%).

[0198] The monomer composition was placed in a stainless steel container measuring 250 mm in width, 250 mm in length, and 30 mm in height, and then irradiated with ultraviolet light for 60 seconds in a UV chamber at 80° C. to cause a crosslinking polymerization reaction (irradiation dose: 10 mV / cm 2 ) and aging for 2 minutes to obtain a crosslinked polymer. The obtained crosslinked polymer was cut into a size of about 5 cm x 5 cm, and then chopped in a chopper to obtain a hydrogel polymer. During the chopping, an aqueous solution of EDTA-4Na (concentration: 40%) was added in an amount of 4000 ppm of EDTA-4Na based on the total weight of the acrylic acid monomer.

[0199] The resulting hydrous gel polymer was dried in a hot air oven at 185°C for 35 minutes, pulverized, and then classified using a standard ASTM mesh sieve to obtain a base resin (BR) powder having a particle size of 150 to 850 μm (particle size of base resin powder: #20 / #30 / #50 / #100 / Pan=0 / 19 / 64 / 16 / 1 (wt%)).

[0200] 100 parts by weight of the obtained base resin powder was mixed with 33 parts by weight of fine powder regranulated material (CRC42, particle size: #20 / #30 / #50 / #100 / Pan=0 / 19 / 64 / 16 / 1 (wt%)) prepared by regranulating fine powder having a particle size of less than 150 μm generated during the drying and pulverizing process with water.

[0201] The mixed powder of the base resin powder and the regranulated fine powder was placed in a surface crosslinking mixer, and then a surface crosslinking solution prepared by mixing 4.7 parts by weight of water, 0.2 parts by weight of ethylene carbonate, 0.05 parts by weight of ACYMA-GK (manufactured by SAN NOPCO KOREA LTD., aqueous solution with a concentration of 50%), and 0.35 parts by weight of an aqueous aluminum sulfate solution (concentration of 35%) based on 100 parts by weight of the base resin powder was added, and the mixture was mixed at a speed of 500 rpm for 30 seconds.

[0202] The resulting mixture was transferred to a jacket-type cylindrical surface reactor equipped with an agitator, and then a surface cross-linking reaction was carried out. The surface cross-linking reaction was carried out until the final superabsorbent resin reached a target CRC value of 40 g / g, and the surface cross-linking reaction time was confirmed after completion of the surface cross-linking reaction. In addition, during the surface cross-linking reaction, the temperature in the reactor was raised to a profile of 184°C after 40 minutes, 181°C after 60 minutes, and 181°C after 80 minutes, based on the start of the surface cross-linking reaction, and thereafter, the surface cross-linking reaction was carried out at 181°C for an additional 10 minutes.

[0203] Thereafter, the surface-treated powder was classified using a standard mesh sieve according to ASTM standards to obtain a highly water-absorbent resin powder having a particle size of 150 to 850 μm.

[0204] Experimental Example 1 The CRC of the base resin powder produced in the process of producing the superabsorbent resin according to the above Examples and Comparative Examples was measured by the following method, and the results are shown in the following table.

[0205] Unless otherwise indicated, all of the following physical property evaluations were carried out at room temperature (25° C.), and saline or salt water refers to a 0.9 wt % sodium chloride (NaCl) aqueous solution.

[0206] (1)Centrifuge Retention Capacity (CRC) Among the base resin powders, those having a particle size of 150 μm to 850 μm were taken, and the Centrifuge Retention Capacity (CRC) was measured based on the water absorption capacity under no load according to the European Disposables and Nonwovens Association (EDANA) standard EDANA WSP241.3.

[0207] Specifically, the base resin powder obtained in each of the examples and comparative examples was classified with a 150 μm to 850 μm sieve to obtain a resin. Such resin W0 (g) (about 0.2 g) was evenly placed in a nonwoven fabric envelope, sealed, and then immersed in physiological saline (0.9 wt%) at room temperature. After 30 minutes, the envelope was drained for 3 minutes under conditions of 250 G using a centrifuge, and the mass W2 (g) of the envelope was measured. In addition, the same operation was performed without using the resin, and the mass W1 (g) at that time was measured. Using each of the obtained masses, CRC (g / g) was calculated according to the following formula 3.

[0208] [Formula 3] CRC(g / g)={[W2(g)-W1(g)] / W0(g)}-1

[0209] In the above formula 3, W0 (g) is the initial weight of the base resin (g); W1(g) is the weight of an envelope measured without using a base resin after immersing the envelope in physiological saline for 30 minutes to absorb it and then spinning it in a centrifuge at 250 G for 3 minutes; W2 (g) is the weight of the envelope including the superabsorbent resin after the base resin is immersed in physiological saline at room temperature for 30 minutes to absorb it, and then centrifuged at 250G for 3 minutes to spin it down.

[0210] Experimental Example 2 The effect of the content of the chelating agent added during the production of the superabsorbent polymer on the antibacterial properties of the superabsorbent polymer was evaluated.

[0211] Specifically, the highly water-absorbent resins were prepared in the same manner as in Example 1-1, except that EDTA-4Na was added in amounts of 0, 3000, 4000, 5000, 5300, 8000, and 13000 ppm based on the total weight of acrylic acid, instead of EDTA.

[0212] The antibacterial properties of the produced highly water-absorbent resin were evaluated by the following method.

[0213] 50ml of artificial urine inoculated with Proteus Mirabilis (ATCC29906) at 3000 CFU / ml was added to 2g of EDTA-free superabsorbent resin, and cultured for 12 hours in an incubator at 35℃. After the culture was completed, the sample was thoroughly washed with 150ml of salt water (0.9% by weight sodium chloride solution) and cultured on a Nutrient Broth Agar (BD DIFCO.) plate to measure the CFU (Colony Forming Unit; CFU / ml), which was calculated as the physical property of the control group.

[0214] In addition, 2g of each superabsorbent resin prepared by varying the amount of EDTA-4Na was added to 50ml of artificial urine inoculated with Proteus Mirabilis (ATCC29906) at 3000CFU / ml and incubated in an incubator at 35℃ for 12 hours. After incubation, 150ml of salt water (0.9wt% sodium chloride solution) was added to the sample and shaken for 1 minute to mix uniformly. The resulting diluted solution was smeared on a Nutrient Broth Agar (BD DIFCO.) plate and incubated in an incubator at 30℃ for 24 hours, after which the CFU (Colony Forming Unit; CFU / ml) was measured and calculated as the physical properties of the experimental group.

[0215] Using the results of each measurement, the bacterial growth inhibition rate defined by the following formula 1 was calculated, and based on this, the antibacterial properties of the superabsorbent resin according to the amount of EDTA-4Na added were evaluated.

[0216] Proteus Mirabilis, the strain of bacteria used to measure the bacterial growth inhibition rate, secretes urease, which breaks down urea in urine to produce ammonia, which causes a foul odor. Therefore, the antibacterial and deodorizing effects of superabsorbent polymers can be properly evaluated based on the Proteus Mirabilis bacterial growth inhibition rate. However, if the growth of Proteus Mirabilis is excessively inhibited for the sake of deodorizing effect, it may kill other beneficial bacteria in the body and cause problems such as skin rashes, so an appropriate level of growth inhibition is necessary.

[0217] [Formula 1] Bacterial growth inhibition rate = [1-{CFU(12h) / CFU control(12h)}]×100(%)

[0218] In the above formula 1, CFU(12h) indicates the number of bacteria grown per unit volume of artificial urine (CFU / ml) when 2g of the superabsorbent resin of the experimental group prepared by adding the chelating agent (EDTA-Na) was added to 50ml of artificial urine inoculated with 3000CFU / ml of Proteus mirabilis (ATCC29906) bacteria and incubated at 35°C for 12 hours. CFU control (12h) indicates the number of bacteria grown per unit volume of artificial urine (CFU / ml) when artificial urine inoculated with the bacteria was cultured under the same conditions on a control superabsorbent resin prepared without adding a chelating agent (EDTA), i.e., the number of bacteria grown per unit volume of artificial urine (CFU / ml) measured for the control group.

[0219] On the other hand, the artificial urine used in this experiment was produced by the following method.

[0220] <Manufacturing artificial urine> 1. Preparation of stock solution The following compounds were mixed to prepare a stock solution, which was then sterilized at 120°C for 15 minutes prior to use.

[0221] Sodium chloride (NaCl) (extra pure (99.0 or higher), Daejung) 8.78g Dipotassium hydrogen phosphate (K2HPO4) (Extra pure (98.0 or higher), Duksan) 4.48g Sodium dihydrogen phosphate (NaH2PO4) (Extra pure (99.0 or higher) Daejung) 1.2g Ammonium chloride (NH4Cl) Extra pure (99.0 or higher, Daejung) 6.68g Sodium sulfate decahydrate (Na2SO4) (Extra pure (98.0 or higher) 6.44g Lactic acid (C3H6O3) (Extra pure (90.0 or higher), manufactured by Daejung) 0.45g Yeast extract (BD Bacto) 20g Distilled water (quaternary distilled water) 1000mL

[0222] 2. Preparation of urea solution The following compounds were mixed and filtered through a 0.22 μm filter to prepare a urea solution.

[0223] Urea (NH2CONH2) (BioReagent (98% or more), Sigma-Aldrich) 36g D-glucose (C6H12 O6) (ACS Reagent, Sigma-Aldrich) 0.18 g Distilled water (quaternary distilled water) 100mL

[0224] 3. Preparation of cationic solution The following compounds were mixed to prepare a cation solution, which was then sterilized at high pressure at 120°C for 15 minutes before use.

[0225] Magnesium chloride hexahydrate (MgCl2.6H2O) (Extra pure (98.0 or higher), Duksan) 1.22g Calcium chloride dihydrate (CaCl2.2H2O) (Extra pure (98.0 or higher), Daejung) 0.67g Distilled water (quaternary distilled water) 20mL

[0226] 4. Manufacturing artificial urine Artificial urine was produced by mixing 940 g of the stock solution produced in steps 1 to 3, 50 ml of the urea solution, and 10 ml of the cation solution. When calculated from the amounts of raw materials of NaCl, urea, and polyvalent metals used in the production of the artificial urine, the NaCl content was about 0.8 wt%, the urea content was about 1.8 wt%, and the polyvalent metal content was about 0.095 wt%, based on the total weight of the produced artificial urine.

[0227] The results of the experiment are shown in Figure 1.

[0228] FIG. 1 is a graph showing the results of measuring the bacterial growth inhibition rate as a function of the amount of a chelating agent (EDTA-Na) added.

[0229] Experimental Example 3 The properties of the superabsorbent resins prepared in the above Examples and Comparative Examples were evaluated as follows, and the results are shown in the following Table.

[0230] Unless otherwise indicated, all of the following physical property evaluations were carried out at room temperature (25° C.), and saline or salt water refers to a 0.9 wt % sodium chloride (NaCl) aqueous solution.

[0231] (1)Centrifuge Retention Capacity (CRC) Except for using the superabsorbent resins produced in the above Examples and Comparative Examples instead of the base resin powder, the centrifugal water retention capacity was measured by the no-load water absorption capacity using EDANA WSP241.3 in the same manner as in (1) of Experimental Example 1.

[0232] Specifically, the superabsorbent resin produced in the examples and comparative examples was classified with a sieve of #30-50 to obtain a resin. Such resin W0(g) (about 0.2g) was evenly placed in a nonwoven fabric envelope, sealed, and then immersed in physiological saline (0.9% by weight) at room temperature. After 30 minutes, the envelope was drained for 3 minutes under conditions of 250G using a centrifuge, and the mass W2(g) of the envelope was measured. In addition, the same operation was performed without using the resin, and the mass W1(g) at that time was measured. Using each of the obtained masses, CRC(g / g) was calculated according to the following formula 3.

[0233] [Formula 3] CRC(g / g)={[W2(g)-W1(g)] / W0(g)}-1

[0234] In the above formula 3, W0 (g) is the initial weight of the superabsorbent polymer (g), W1(g) is the weight of the envelope measured after immersing the envelope in physiological saline for 30 minutes to absorb the water without using a superabsorbent resin, and then spinning the envelope at 250 G for 3 minutes using a centrifuge. W2 (g) is the weight of the envelope including the superabsorbent polymer after the superabsorbent polymer is immersed in saline at room temperature for 30 minutes to absorb the polymer, and then centrifuged at 250G for 3 minutes to spin the polymer.

[0235] (2) Absorbency Under Pressure (AUP) The water absorption capacity of each resin under pressure at 4826 Pa (0.7 psi) was measured by EDANA method WSP242.3-10. The resin-classified powder used in the CRC measurement was used for measuring the water absorption capacity under pressure.

[0236] Specifically, a stainless steel wire mesh of 400 mesh was attached to the bottom of a plastic cylinder with an inner diameter of 25 mm. Under conditions of room temperature and humidity of 50%, water-absorbent resin W0(g) (0.16 g) was evenly spread on the wire mesh, and a piston capable of evenly applying a load of 4826 Pa (0.7 psi) on the wire mesh was made to be slightly smaller than the outer diameter of 25 mm, with no gap between it and the inner wall of the cylinder, and to ensure that the piston's vertical movement was not hindered. At this time, the weight W3(g) of the device was measured.

[0237] A glass filter with a diameter of 90 mm and a thickness of 5 mm was placed inside a petroleum dish with a diameter of 150 mm, and physiological saline solution consisting of 0.9% by weight of sodium chloride was placed at the same level as the upper surface of the glass filter. A sheet of filter paper with a diameter of 90 mm was placed on top of the glass filter. The measuring device was placed on the filter paper, and the liquid was absorbed under a load for one hour. After one hour, the measuring device was lifted and its weight W4 (g) was measured.

[0238] Using the obtained masses, the water absorption capacity under pressure (g / g) was calculated according to the following formula.

[0239] [Formula 4] AUP(g / g)=[W4(g)-W3(g)] / W0(g)

[0240] (3)EFFC (arithmetic mean of centrifugal water retention capacity and pressurized water absorption capacity) For the superabsorbent resins prepared in the Examples and Comparative Examples, EFFC was calculated according to the following Equation 2.

[0241] [Formula 2] EFFC=(CRC+AUP) / 2

[0242] In the above formula 2, CRC is the water retention capacity of a superabsorbent polymer in physiological saline (0.9% by weight sodium chloride aqueous solution) after centrifugation for 30 minutes, measured by EDENA method WSP241.3. AUP is the pressurized water absorption capacity of a superabsorbent polymer for one hour under 4826 Pa (0.7 psi) in physiological saline (0.9 wt % sodium chloride aqueous solution) as measured by EDANA method WSP242.3-10.

[0243] (4) Residual Monomers (RM, Residual Monomers, ppm) The residual monomer content of the superabsorbent resins prepared in the Examples and Comparative Examples was measured by EDANA WSP210.2 method.

[0244] Specifically, 1.000 g of a superabsorbent resin powder sample having a particle size of 150 to 850 μm and 184.3 g of a 0.90 wt % sodium chloride aqueous solution were placed in a 250 ml plastic container with a lid and stirred for 1 hour to extract the unreacted acrylic acid. The extracted solution was analyzed using HPLC / CAD under the following conditions to measure the content of unreacted acrylic acid in the residual monomer (based on the total weight of the superabsorbent resin, ppm).

[0245] <Analysis conditions> *Mobile phase - Mobile phase A: 1000 mL of acetonitrile was filtered through a solvent clarification system to remove foreign matter. - Mobile phase B: 1000 mL of ultrapure water was filtered through a solvent clarification system to remove foreign matter.

[0246] *HPLC analysis conditions -Column: Capcellpak C18 (4.6mm ID x 50mm L., 3μm, Shiseido) -Eluent: Mobile phase A / Mobile phase B=75 / 25 (v / v, %) -Flow rate: 1mL / min -Column temperature: 40℃ -Run time: 15 minutes -Injection Volume: 10μl

[0247] *CAD analysis conditions -Gas pressure = 232,353Pa (33.7psi), Corona = normal -Total flow=1.14mL / min, Flow ratio=0.48 -Range was measured at 100 pA, and then adjusted according to the content.

[0248] (The magnitude of the peak increases as the value goes from 100pA to 50pA to 20pA.)

[0249] (5) Hunter Color (B) The b value was measured using a colorimeter (Color Quest II, Hunter Lab Co.).

[0250] L, a, and b measured by a colorimeter each represent a value on a coordinate axis that indicates a specific color. L represents whiteness (brightness, luminosity) and can have a value from 0 to 100. The closer the L value is to 0, the blacker the color is, and the closer it is to 100, the whiter the color is. a can have integers and negative numbers based on 0, but the greater the value, the more red the color is, and the smaller the value, the more green the color is. b can have integers and negative numbers based on 0, but the greater the value, the more yellow the color is, and the smaller the value, the more blue the color is.

[0251] (6) Antibacterial properties The antibacterial activity against Proteus Mirabilis (ATCC29906) was evaluated in the same manner as in Experimental Example 2, except that the superabsorbent polymers prepared in the Examples and Comparative Examples were used instead of the superabsorbent polymers in the experimental group.

[0252] (7) Chelating agent content analysis The content of the chelating agent in the superabsorbent resins produced in the above Examples and Comparative Examples was measured by the method described below (based on the total weight of the superabsorbent resin, ppm).

[0253] <Analysis method> 1.extraction Method type: Preparation method - Solvent extraction 1) 100 mL of 0.9% NaCl aqueous solution was added to 0.5 g of the superabsorbent resin produced in the above Examples or Comparative Examples, and EDTA-4Na was extracted to prepare each sample.

[0254] 2.HPLC / UV analysis For HPLC / UV analysis, a Waters 1525 Binary HPLC Pump (Waters) and a Waters 2489 UV / Visible Detector (Waters) were used.

[0255] 2.1 Method types: Measurement methods - quantitative analysis 1) The instrument was stabilized, and standard samples were injected to create a calibration curve. At this time, the standard samples used were prepared by dissolving EDTA in 100 mL of 0.9% NaCl aqueous solution at concentrations of 1000, 3000, 4000, 5000, 6000, 7000, 8000, 10000, and 13000 ppm.

[0256] 2) The sample prepared in 1) of the extraction procedure above was injected into the instrument, and the content of the chelating agent EDTA was calculated using the calibration curve.

[0257] 3) HPLC conditions -Column: PRP-1 (Hamilton) (4.6 mm ID x 150 mm L, 5 μm) -UV detection wavelength: 210nm -Mobile phase: 3.42g H3PO4 + 4L H2O (85%), pH=2.5 -Gradient elution: 0.0074mol H3PO4 -Flow rate: 0.8mL / min -Column temperature: 40℃ -Injection volume: 10 μL -Run time: 20 min.

[0258] FIG. 2 is a graph showing the results of observing, by HPLC analysis, the change in the amount of chelating agent detected in a superabsorbent resin depending on the amount of chelating agent added during the production of the superabsorbent resin.

[0259] [Table 1] [Table 2]

[0260] In Tables 1 and 2, "ppm" of a is based on the total weight of the acrylic monomer (AA), and "ppm" of b is based on the total weight of the final superabsorbent polymer (SAP).

[0261] As a result of the experiment, when a chelating agent was not used during the production of the superabsorbent polymer, or when the amount of the chelating agent added was too small beyond the amount of the chelating agent defined in the present invention, the antibacterial effect was significantly reduced (Comparative Examples 1-1, 1-2, 1-3, 2-1, and 2-4). On the other hand, the antibacterial effect increased as the amount of the chelating agent added increased, but when the amount of the chelating agent added exceeded a certain level, the increase in the antibacterial effect was not as large as the amount of the chelating agent added, and rather the water absorption performance of the superabsorbent polymer, especially the EFFC, was reduced due to the excess chelating agent. This confirmed that the amount of the chelating agent added must be controlled in order to fully achieve the effect of improving the antibacterial effect while maintaining excellent water absorption performance.

[0262] In addition, when the persulfate was added at an excessively high content, exceeding the amount of persulfate added as defined in the present invention, the Hunter color B value of the superabsorbent polymer increased significantly (Comparative Example 2-3).In contrast, when the persulfate was added at an excessively low content, exceeding the amount of persulfate added as defined in the present invention, the amount of residual monomer increased significantly (Comparative Example 2-2).

Claims

1. a base resin powder comprising a first crosslinked polymer of a water-soluble ethylenically unsaturated monomer having at least a partially neutralized acidic group, and a chelating agent; and a surface crosslinked layer formed on the base resin powder and including a second crosslinked polymer obtained by additionally crosslinking the first crosslinked polymer via a surface crosslinking agent; The following conditions (i) to (iii) are satisfied: Super absorbent resin: (i) When 2 g of a superabsorbent resin was added to 50 ml of artificial urine inoculated with 3,000 CFU / ml of Proteus mirabilis (ATCC29906) bacteria and incubated at 35°C for 12 hours, the number of bacteria grown per unit volume of artificial urine (CFU / ml) was 10 CFU (12h). 9 below (ii) Residual monomer content measured by EDANA method WSP210.3: 450 ppm or less (iii) Hunter color B: 10 or less.

2. The superabsorbent resin has a bacterial growth inhibition rate of 95% or more, as represented by the following formula 1: The highly water-absorbent polymer according to claim 1: [Formula 1] Bacterial growth inhibition rate = [1-{CFU (12h) / CFU control (12h)}] x 100 (%) In the above formula 1, CFU(12h) indicates the number of bacteria (CFU / ml) per unit volume of artificial urine when 2g of superabsorbent resin is added to 50ml of artificial urine inoculated with Proteus mirabilis (ATCC29906) bacteria at 3000 CFU / ml and the mixture is cultured at 35°C for 12 hours, and CFU control(12h) indicates the number of bacteria (CFU / ml) per unit volume of artificial urine when the control superabsorbent resin is cultured under the same conditions with the above bacteria inoculated artificial urine, The control superabsorbent resin refers to the same superabsorbent resin as the control superabsorbent resin, except that the base resin powder does not contain a chelate.

3. The superabsorbent resin further satisfies the following conditions (iv) to (vi): The highly water-absorbent polymer according to claim 1: (iv) Centrifugation retention capacity (CRC) measured by EDENA method WSP241.3: 39 g / g or more (v) Absorbency under pressure (AUP) at 4826 Pa (0.7 psi) measured by the EDANA method WSP242.3-10: 17 g / g or more (vi) The arithmetic mean of the centrifugal water retention capacity and the pressurized water absorption capacity (EFFC), represented by the following formula 2: 28 or more [Formula 2] EFFC=(CRC+AUP) / 2 In the above formula 2, CRC is the water retention capacity of the superabsorbent polymer in physiological saline (0.9 wt % sodium chloride aqueous solution) after centrifugation for 30 minutes, measured by EDENA method WSP241.3; AUP is the water absorption capacity of a superabsorbent polymer under pressure of 4826 Pa (0.7 psi) for one hour in physiological saline (0.9 wt % aqueous sodium chloride solution) as measured by EDANA method WSP242.3-10.

4. The chelating agent is present in the base resin powder or dispersed on the surface of the base resin powder. The highly water-absorbent resin according to claim 1.

5. The chelating agent is at least one selected from the group consisting of ethylenediaminetetraacetic acid, diethylenetriaminepentaacetic acid, phenolic acid, citric acid, amino acids, and salts thereof. The highly water-absorbent resin according to claim 1.

6. The chelating agent is contained in an amount of 4,500 to 12,000 ppm based on the total weight of the superabsorbent resin. The highly water-absorbent resin according to claim 1.

7. The base resin powder further comprises a persulfate. The highly water-absorbent resin according to claim 1.

8. The persulfate salt includes one or more of sodium persulfate and potassium persulfate. The highly water-absorbent resin according to claim 7.

9. A step of cross-linking and polymerizing a water-soluble ethylenically unsaturated monomer having at least a partially neutralized acidic group in the presence of an internal cross-linking agent and a persulfate, followed by chopping to form a hydrogel polymer; drying and grinding the hydrogel polymer to form a base resin powder; and heat treating the base resin powder in the presence of a surface cross-linking agent to cross-link the surface of the base resin powder; The persulfate is added in an amount of 1,800 to 3,500 ppm based on the total weight of the water-soluble ethylenically unsaturated monomer; In one or more steps of the cross-linking polymerization and chopping, a chelating agent is added in an amount of 6,000 to 15,000 ppm based on the total weight of the water-soluble ethylenically unsaturated monomer; A method for producing the highly water-absorbent resin according to claim 1.

10. The persulfate salt includes one or more of sodium persulfate and potassium persulfate. A method for producing the highly water-absorbent resin according to claim 9.

11. The chelating agent is at least one selected from the group consisting of ethylenediaminetetraacetic acid, diethylenetriaminepentaacetic acid, phenolic acid, citric acid, amino acids, and salts thereof. A method for producing the highly water-absorbent resin according to claim 9.

12. A chelating agent is added during the crosslinking polymerization, The weight ratio of the persulfate to the chelating agent is 1:3 to 1:4; A method for producing the highly water-absorbent resin according to claim 9.

13. During the chopping, a chelating agent is added, The weight ratio of the persulfate to the chelating agent is 1:2 to 1:7; A method for producing the highly water-absorbent resin according to claim 9.

14. The chopping is performed using a chopper. A method for producing the highly water-absorbent resin according to claim 9.

15. The surface crosslinking agent is at least one selected from the group consisting of polyhydric alcohol compounds; epoxy compounds; polyamine compounds; haloepoxy compounds; condensation products of haloepoxy compounds; oxazoline compounds; mono-, di- or polyoxazolidinone compounds; cyclic urea compounds; polyvalent metal salts; and alkylene carbonate compounds. A method for producing the highly water-absorbent resin according to claim 9.

16. The method further includes a step of mixing the fine powder regranulated material in an amount of 20 to 40 parts by weight based on 100 parts by weight of the base resin powder before the surface crosslinking. A method for producing the highly water-absorbent resin according to claim 9.

17. An article comprising the superabsorbent polymer of claim 1.

18. The article of claim 17, wherein the article is a hygiene product.

Citation Information

Patent Citations

  • Water-absorbing resin and absorptive article

    JP2016028118A

  • Superabsorbent resin composition

    JP2020528945A

  • Highly water-absorbent resin and method for producing the same

    JP2022509877A

  • Polyacrylic acid (SALT) water-absorbent resin powder, and method for producing same

    WO2013002387A1